The Influence of Soil Moisture on the Water Balance of Tobacco Plant. (I): The Influence of Soil Moisture Level on the Senescence of Tobacco Leaves - KUME, Hideo (Environment Control in Biology, 1973)
Two tabacco varieties, H-2 and MC, were grown in lysimeters (2m×2m×1.2 m), with different soil moisture levels. The former variety is resistant to high soil moisture level, the latter one is a new variety subject to defoliation of order leaves by high soil moisture level. Soil moisture levels were changed at three growing stages, i.e. early, middle and late stage. Thus HLL plot, for example, means the plot where the soil moisture level was high at early stage, low at middle and at late stage. Similar abbreviation is used in Table 1 and elsewhere. Soil moisture stress in terms ofpF, osmotic potential (formerly osmotic pressure) of leaf sap, and water potential (formerly suction force or DPD) of leaf discs were determined. Growth of tabacco plants, nitrogen and nicotine content of leaves were also investigated. The results obtained were summarized as follows: 1) After the rainfall more than 30 mm/day, soil moisture remarkably increased (Fig. 1) . But such cases occurred only thrice or four times throughout the growing stages, so the moisture stress was maintained for the most part at the level expected (high moisture, pF=1.7; middle moisture, pF=2.0; low moisture, pF=2.5) . 2) In HLL plot, where rain water was intercepted by rainshelter, the least defoliation ratio was observed even in MC (Table 4) . 3) Smaller pressure potential or turgor pressure was found in the lower leaves of MC than that of H-2 (Fig. 3) . The decrease of pressure potential was closely related to senescence of leaves. 4) In MC, the chlorophyll content of the lower leaves was higher in HLL plot than in other plots This fact coincided well with the slow rate of senescence of leaves in HLL plot (Fig. 6) . 5) Total nitrogen and nicotine content increased in both MC and H-2 by decreasing soil moisture after topping. The increase of nitrogen and nicotine content in MC was smaller than that of H-2 (Table 5) .